Nano‐Composites for Water Remediation: A Review. (28th July 2014) - Tesh, Sarah J.; Scott, Thomas B.
<x xml:space="preserve">Abstract</x> As global populations continue to increase, the pressure on water supplies will inevitably intensify. Consequently the international need for more efficient and cost effective water remediation technologies will also rise. The introduction of nano‐technology into the industry may represent a significant advancement and zero‐valent iron nano‐particles (INPs) have been thoroughly studied for potential remediation applications. However, the application of water dispersed INP suspensions is limited and somewhat contentious on the grounds of safety, whilst INP reaction mechanisms, transport properties and ecotoxicity are areas still under investigation. Theoretically, the development of nano‐composites containing INPs to overcome these issues provides the logical next step for developing nano‐materials that are better suited to wide application across the water industry. This review provides an overview of the range of static, bulk nano‐composites containing INPs being developed, whilst highlighting the limitations of individual solutions, overall classes of technology, and lack of comparative testing for nano‐composites. The review discusses what further developments are needed to optimize nano‐composite water remediation systems to subsequently achieve commercial maturity.